2008
DOI: 10.30638/eemj.2008.098
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Contamination From Waste Storage Works

Abstract: Groundwater is an important source of drinking water, especially for rural population. In the last years, bacteria, nitrate, organic chemicals and other pollutants existing in groundwater have increased public concern about the quality of groundwater. Groundwater provides about 22% of all freshwater withdrawals; 37% of agricultural use (mostly for irrigation); 37% of the public water supply withdrawals; 51% of all drinking water for the total population and 99% of drinking water for the rural population; 46% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The relationship between alkalinity and the group III lakes is interesting and may be an effect of pollution which altered their chemistry, in the northern Moldavia area where agriculture effects and a lack of water dilution occur [73,74].…”
Section: Lakes' Fish Species-environment Variables Clustersmentioning
confidence: 99%
“…The relationship between alkalinity and the group III lakes is interesting and may be an effect of pollution which altered their chemistry, in the northern Moldavia area where agriculture effects and a lack of water dilution occur [73,74].…”
Section: Lakes' Fish Species-environment Variables Clustersmentioning
confidence: 99%
“…International studies show that communal sewage is one of the most significant sources of pollution in addition to industrial and agricultural activities, the treatment and purification of which is often unresolved for developed and developing countries [2][3][4][5][6]. Several studies specified that the lack of sewage treatment systems in rural areas causes sewage to enter groundwater, resulting in a severe degradation in groundwater quality in these areas [7][8][9][10]. Having reviewed the international literature, we found that although publications have been published regarding the environmental problems caused by sewage generated in settlements, a comprehensive investigation that would present the water quality before and after the construction of the sewerage network covering an entire town has not yet been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Por lo tanto, este residuo debe tener una disposición especial en celdas de seguridad, donde estas estructuras, además de representar un gasto adicional para las empresas, demandan grandes extensiones de terreno. Sin embargo, la mayor preocupación radica en que estas celdas se pueden degradar con el paso del tiempo y liberar los contaminantes confinados; lo que representa un potencial peligro de contaminación de los suelos, las aguas superficiales y subterráneas a sus alrededores (6) .…”
Section: Introductionunclassified